(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the importance and future prospects of ensuring inter-ethnic harmony and solidarity in the society, its necessity, current issue, and in this process, its socio-philosophical, moral, spiritual, legal classification and specific features are analyzed.